Nonapoptotic caspase-3 guides C1q-dependent synaptic phagocytosis by microglia - Megumi Andoh; Natsuki Shinoda; Yusuke Taira; Tasuku Araki; Yuka Kasahara; Haruki Takeuchi; Masayuki Miura; Yuji Ikegaya; Ryuta Koyama (Nature Communications)
Abstract Caspases are known to mediate neuronal apoptosis during brain development. However, here we show that nonapoptotic activation of caspase-3 at presynapses drives microglial synaptic phagocytosis. Real-time observation and spatiotemporal manipulation of synaptic caspase-3 in the newly established, mouse-derived culture system demonstrate that increased neuronal activity triggers localized presynaptic caspase-3 activation, facilitating synaptic tagging by complements. High-resolution live imaging reveals that caspase-3 activation promotes synapse-selective complement-dependent microglial phagocytosis without axonal shearing. Furthermore, activity-dependent caspase-3 activation at inhibitory presynapses induces microglial phagocytosis in mice and increases seizure susceptibility. This increased susceptibility is reversed by genetic depletion of microglial complement receptors. Thus, localized, nonapoptotic caspase activity guides complement-dependent microglial synaptic phagocytosis and remodels neuronal circuits.